2015
DOI: 10.4314/ajtcam.v12i4.20
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged heating of honey increases its antioxidant potential but decreases its antimicrobial activity

Abstract: Background: Honey is renowned for its antioxidant, antimicrobial and medicinal properties. It is typically heated and filtered during processing to avoid crystallization. However, few studies have reported its heating effect and the antioxidant and antimicrobial activities of honey. Materials and Methods: In this study, honey samples were collected from eight different honey-producing sites in Bangladesh and heated to 50ºC, 70ºC and 90ºC for 12 hours, while the antioxidant potentials and antimicrobial properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 35 publications
3
20
1
Order By: Relevance
“…Similar studies were obtained by Jahan et al, who investigated the influence of heat treatment on the biological proprieties in Bangladesh honey [7].…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Similar studies were obtained by Jahan et al, who investigated the influence of heat treatment on the biological proprieties in Bangladesh honey [7].…”
Section: Introductionsupporting
confidence: 58%
“…Nevertheless, thermal treatment can result in some compounds changes in honey. In a recent study, Jahan et al observed that the total phenol content increased with treatments at temperatures between 50, 70 and 90 °C for 12 h of drying process for Bangladesh honey [7].…”
Section: Discussionmentioning
confidence: 99%
“…The extract that was heated at 65 o C has the greatest inhibition zone diameter than the other treatments. This was caused by the activation of flavonoids that was heated up to 70 o C [32]. This study has a similar result, which heating at 75, 85, and 95 o C would lead to damage of the active compounds, causing the inhibition zone diameter to decrease [32].…”
Section: G Stability Of Selected Extract Against Heating Temperaturesupporting
confidence: 52%
“…This was caused by the activation of flavonoids that was heated up to 70 o C [32]. This study has a similar result, which heating at 75, 85, and 95 o C would lead to damage of the active compounds, causing the inhibition zone diameter to decrease [32]. Extract that was heated at 95 o C has the lowest inhibition zone diameter, which shows that the antimicrobial compounds are damaged.…”
Section: G Stability Of Selected Extract Against Heating Temperaturementioning
confidence: 52%
“…Proline is the prominent amino acid found in different types of honey. The main enzymes and amino acids identified in honey from different botanical and geographical origins are listed in Table 3 [14,21,[60][61][62]. Proline is reported to mainly originate from bee salivary secretions during the conversion of nectar into honey.…”
Section: Honey Proteins and Enzymes Provide Digestive Benefits And Himentioning
confidence: 99%